Implementation of fractional order filters discretized by modified Fractional Order Darwinian Particle Swarm Optimization - Ates, Abdullah; Alagoz, Baris Baykant; Kavuran, Gurkan; Yeroglu, Celaleddin (Elsevier Sci Ltd, 2017)
Digital systems are placed at the core of information technology and they are used extensively in electronics. The digital filter realization has become a central topic of signal processing studies. This paper presents a discrete IIR filter design method for approximate realization of fractional order continuous filters in digital systems. For this purpose, Fractional Order Darwinian Particle Swarm Optimization (FODPSO) method is modified to provide better fitting of a discrete IIR filter function to a fractional order continuous filter and we implemented a hybrid version of FODPSO method, where the initial particle generation is carried out by arithmetical candidate point selection technique of the Base Optimization Algorithm (BaOA). This modification expands the search range of the FODPSO and thus the optimized discrete IIR filter can provide better approximation to amplitude response of fractional order continuous filter functions. In the paper, several illustrative examples are presented to demonstrate the performance of proposed methods. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Fractional order filter; Discrete realization; Optimization; Particle swarm